Functional traits of tree species in a fragment of Araucaria forest in Lages, Santa Catarina state Atributos funcionais de espécies arbóreas em um fragmento de floresta Ombrófila mista em Lages-SC - Missio F.F.* (2017)
© 2017, Universidade Federal de Santa Maria. All rights reserved.This study aimed to describe the functional traits of tree species in an Araucaria Forest fragment, in the municipality of Lages, SC state, in order to group them functionally. For each of the 20 most abundant species in the study area, a total of 10 individuals were sampled for the determination of the mean wood density and mean leaf size. The leaf renovation regimes, the dispersal syndrome and the maximum height in the fragment were also described for these species. The results of maximum height and wood density suggest the existence of a trade-off between investment of resources in height growth, ensuring access to some higher light availability, or in wood density, allowing for greater resilience and survival in a shaded understory environment. The gymnosperm species, Podocarpus lambertii and Araucaria angustifolia showed smaller leaves, while Cupania vernalis, Jacaranda puberula and Matayba elaeagnoides, all of compound leaves, had larger ones. Four functional groups stood out: 1) Evergreen with large leaves, 2) Evergreen with small leaves, 3) Deciduous with zoochoric syndrome, and 4) Deciduous with non- zoochoric syndrome. The results showed that the most abundant species of the studied Araucaria Forest fragment present functional trait variations, suggesting different life strategies.